Enhanced gas-liquid mass transfer of an oscillatory constricted-tubular reactor - Reis, N. (2008)
The mass transfer performance has been tested for gas-liquid flow in a new tubular reactor system, the oscillating mesotube (OMT), which features the oscillatory movement of fluid across a series of smooth constrictions located periodically along the vertical 4.4 mm internal diameter tube. The effect of the fluid oscillations (frequency,f, and center-to-peak amplitude, x(0), in the range of 0-20 s(-1) and 0-3 mm, respectively) on the overall volumetric mass transfer coefficient (k(L)a) has been tested by measuring the oxygen saturation levels with a fiber-optical microprobe (oxygen micro-optrode), and a mathematical model has been produced to describe the oxygen mass transport in the OMT. The oxygen mass transfer rates were about I order of magnitude higher (k(L)a values up to 0.16 s(-1)) than those values reported for gas-liquid contacting in a 50 mm internal diameter oscillatory flow reactor (OFR), for the same peak fluid oscillatory velocity, i.e., 2 pi fx(0). This represents remarkable oxygen transfer efficiencies, especially when considering the very low mean superficial gas velocity involved in this work (0.37 mm s(-1)). The narrower constrictions helped to increase the gas fraction (holdup) by reducing the rise velocity of the bubbles. However, the extent of radial mixing and the detachment of vortex rings from the surface of the periodic constrictions are actually the main causes of bubbles retention and effective gas-liquid contacting and are, thus, responsible for the enhancement of k(L)a in the OMT.